Measuring the intensity of community programs and policies for preventing childhood obesity in a diverse sample of US communities: the Healthy Communities Study. (14th June 2018) - Collie‐Akers, V. L.; Schultz, J. A.; Fawcett, S. B.; Landry, S.; Obermeier, S.; Frongillo, E. A.; Forthofer, M.; Weinstein, N.; Weber, S. A.; Logan, A.; Arteaga, S. S.; Nebeling, L.; et al.
Summary: Introduction: Efforts to address the critical public health problem of childhood obesity are occurring across the USA; however, little is known about how to characterize the intensity of these efforts. Objectives: The purposes of this study are to describe the intensity of community programs and policies (CPPs) to address childhood obesity in 130 US communities and to examine the extent to which observed CPPs targeted multiple behaviours and employed a comprehensive array of strategies. Methods: To document CPPs occurring over a 10‐year period, key informants were interviewed using a semi‐structured interview protocol. Staff coded CPPs for key characteristics related to intensity, including reach, duration and strategy. Three types of CPP scores were calculated for intensity of CPPs, targeting of CPPs towards multiple behaviours and strategies used. Results: Nine thousand six hundred eighty‐one CPPs were identified. On average, communities had 74 different CPPs in place (standard deviation 30), with variation in documented CPPs (range 25–295). Most communities experienced a steady, modest increase in intensity scores over 10 years. CPP targeting scores suggested that communities expanded the focus of their efforts over time to include more behaviours and strategies. Conclusions: Findings of this large‐scale study indicate that great variation exists across communities in the intensity and focus of community interventions being implemented to address childhood obesity. Abstract : What is already known about this subject? Communities are implementing programs and policies to address childhood obesity. Little is known about how these programs and policies vary in intensity. Similarly, little is understood about how communities are focusing their efforts by targeting key behaviours or strategies. What this study adds? This study describes the creation of three types of indices for understanding how community programs and policies may contribute to prevention of childhood obesity. Across 130 communities in the USA, implementation of community programs and policies has varied considerably. Findings suggest that, over the last 10 years, intensity and the targeting of specific behaviours and strategies have grown steadily. This article is part of the supplement: The Healthy Communities Study: Examining Community Programs, Policies and Other Characteristics in Relation to Child Weight, Diet, and Physical Activity